Fiber-1 of serotype 4 fowl adenovirus mediates superinfection resistance against serotype 8b fowl adenovirus - Lu, Hao; Guo, Yiwen; Xu, Zhenqi; Wang, Weikang; Lian, Mingjun; Li, Tuofan; Wan, Zhimin; Shao, Hongxia; Qin, Aijian; Xie, Quan; Ye, Jianqiang (Frontiers in Microbiology, 2022)
In recent years, hepatitis-hydropericardium syndrome (HHS) and inclusion body hepatitis (IBH) caused by serotype 4 fowl adenovirus (FAdV-4) and serotype 8b fowl adenovirus (FAdV-8b), respectively, are widely prevalent in China, causing huge economic losses to poultry industry. Numerous studies have revealed the mechanism of the infection and pathogenesis of FAdV-4. However, little is known about the mechanism of the infection of FAdV-8b. Among the major structural proteins of fowl adenoviruses, Fiber is characterized by the ability to recognize and bind to cellular receptors to mediate the infection of host cells. In this study, through superinfection resistance analysis and an interfering assay, we found that Fiber-1 of FAdV-4, rather than Hexon, Penton, and Fiber of FAdV-8b, conferred efficient superinfection resistance against the infection of FAdV-8b in LMH cells. Moreover, the truncation analysis depicted that the shaft and knob domains of FAdV-4 Fiber-1 were responsible for the inhibition. However, knockout of coxsackie and adenovirus receptor (CAR) in LMH cells inhibited the replication of FAdV-8b only at early time points, indicating that CAR might not be the key cell receptor for FAdV-8b. Overall, our findings give novel insights into the infection mechanism of FAdV-8b and provide a new target for the prevention and control for both FAdV-4 and FAdV-8b.